Ipatasertib plus paclitaxel for PIK3CA/AKT1/PTEN-altered hormone receptor-positive HER2-negative advanced breast cancer: primary results from cohort B of the IPATunity130 randomized phase 3 trial - Turner, Nicholas; Dent, Rebecca A.; O’Shaughnessy, Joyce; Kim, Sung-Bae; Isakoff, Steven J.; Barrios, Carlos; Saji, Shigehira; Bondarenko, Igor; Nowecki, Zbigniew; Lian, Qinshu; Reilly, Sarah-Jayne; Hinton, Heather; et al. (Breast Cancer Research and Treatment, 2022)
Purpose PI3K/AKT pathway alterations are frequent in hormone receptor-positive (HR+) breast cancers. IPATunity130 Cohort B investigated ipatasertib–paclitaxel in PI3K pathway-mutant HR+ unresectable locally advanced/metastatic breast cancer (aBC). Methods Cohort B of the randomized, double-blind, placebo-controlled, phase 3 IPATunity130 trial enrolled patients with HR+ HER2-negative PIK3CA / AKT1/PTEN -altered measurable aBC who were considered inappropriate for endocrine-based therapy (demonstrated insensitivity to endocrine therapy or visceral crisis) and were candidates for taxane monotherapy. Patients with prior chemotherapy for aBC or relapse < 1 year since (neo)adjuvant chemotherapy were ineligible. Patients were randomized 2:1 to ipatasertib (400 mg, days 1–21) or placebo, plus paclitaxel (80 mg/m 2 , days 1, 8, 15), every 28 days until disease progression or unacceptable toxicity. The primary endpoint was investigator-assessed progression-free survival (PFS). Results Overall, 146 patients were randomized to ipatasertib–paclitaxel and 76 to placebo–paclitaxel. In both arms, median investigator-assessed PFS was 9.3 months (hazard ratio, 1.00, 95% CI 0.71–1.40) and the objective response rate was 47%. Median paclitaxel duration was 6.9 versus 8.8 months in the ipatasertib–paclitaxel versus placebo–paclitaxel arms, respectively; median ipatasertib/placebo duration was 8.0 versus 9.1 months, respectively. The most common grade ≥ 3 adverse events were diarrhea (12% with ipatasertib–paclitaxel vs 1% with placebo–paclitaxel), neutrophil count decreased (9% vs 7%), neutropenia (8% vs 9%), peripheral neuropathy (7% vs 3%), peripheral sensory neuropathy (3% vs 5%) and hypertension (1% vs 5%). Conclusion Adding ipatasertib to paclitaxel did not improve efficacy in PIK3CA/AKT1/PTEN -altered HR+ HER2-negative aBC. The ipatasertib–paclitaxel safety profile was consistent with each agent’s known adverse effects. Trial registration NCT03337724.